Site Suitability Analysis for Provision of Ecosystem Services for Sustainable Waterfront Development - Mazed Parvez; Md Sazzadul Karim; A H Md Mahabub Nawaz; Syed Tanim Ahmed; Faisal M Ahamed; Md Fazle Rabby; Laila Begum (Humanities, Society, and Community, 2024)
The "area of a town near an area of water, such as a river or the sea" and "the interface between land and water" were two ways to define the urban waterfront. This study aimed to shed light on the pressing issue of management service deficits within canal environments, emphasizing the detrimental consequences of canal encroachment, such as heightened flood vulnerability, dwindling groundwater recharge, and the loss of ecosystems and biodiversity. Based on these issues, the study identified suitable sites for sustainable waterfront development by conducting an in-depth analysis and employing geospatial mapping techniques. The criteria included proximity to water bodies, flora and fauna, urban green space, urban built-up areas, urban fellow land, and road access, and utilized GIS, KII, and community people consultations. The study addressed the practical challenges that the capital cities of Bangladesh and similar cities worldwide face in reconciling the demands of urban development with ecological conservation. The study’s aims, new findings, and contributions to the current literature are integral to advancing the discourse on sustainable urban development. Among the 4,316 evaluated locations, 50% were deemed entirely suitable, 37% predominantly suitable, and the remaining locations had lower suitability levels, including 10% slightly acceptable and none moderately suitable. This research provides actionable insights to inform urban planners, policymakers, and researchers on the creation of resilient and competitive urban regions by addressing the urgent need for holistic solutions that balance environmental preservation, social equity, and economic viability.